Understanding debates about Asiatic cheetah conservation through media analysis. Issue 7 (19th May 2022) - Nayeri, Danial; Hosseini, Mahshid; Gore, Meredith; Farhadinia, Mohammad S.
Abstract: Given the global popularity and ubiquity of electronic media coverage of wildlife and conservation, media frame analysis is widely used to help conservation decision‐makers understand public opinion, differing goals and priorities, and arguments used in conflict. Nonetheless, media frame analysis has only been used on occasion to elucidate how different conservation stakeholders frame wildlife management plans. We applied media frame analysis to the case of critically endangered Asiatic cheetah ( Acinonyx jubatus venaticus ), one of the world's rarest felids now confined to Iranian deserts. Between January 2018 and December 2020, 91 interviews from 44 conservation stakeholders were published in Persian‐language electronic media following the development of an Asiatic cheetah management plan. Media framed conservationists as agreeing on the alarming situation of Asiatic cheetahs and high‐level interventions needed for possible recovery yet disagreeing about using integrated (in situ + ex situ) versus single management approaches (in situ only) between academic and NGO interviewees. Interviews presented a balance of thematic (year‐round) and episodic around National and International Cheetah Days. We also found that the current media debate was highly skewed toward non‐local perspectives while views from reserve staffs were rarely ( n = 2) reflected in the media. The increasing number of controversial conservation topics in media debates can persuade the public or policymakers by setting agenda. Disagreement in premises, threats and interventions confuse managers and potentially creates procrastination of necessary actions. Higher inclusion of reserve staffs, technical cooperation between stakeholders and pursuing the existing management plan are interventions that may portend great potential to enhance the conservation impact of media debates.